Out-of-plane behavior of stone masonry walls: Experimental and numerical analysis - Maccarini, Helena (2018)
Aiming at contributing to the better understanding of the out-of-plane behavior of unreinforced stone masonry structures, this paper presents the results of an experimental and numerical campaign performed on two U-shaped walls with different masonry bonds representative of Portuguese vernacular architecture. The experimental campaign included non-destructive tests for the material characterization and an out-of-plane cyclic loading test for the characterization of the out-of-plane response. A finite element numerical model was constructed, calibrated with the experimental results, which allowed performing a nonlinear parametric study to evaluate the most influential material and geometrical parameters in the out-of-plane behavior of stone masonry walls.